Blastocystis and urticaria: Examination of subtypes and morphotypes in an unusual clinical manifestation (2015)
Blastocystis is a human common enteric protist that may colonize a large variety of non-human hosts linked to symptoms and diseases such as abdominal pain, constipation, diarrhea, urticaria, flatulence and irritable bowel syndrome (IBS). Blastocystis exhibits remarkable genetic diversity and multiple subtypes (STs) within the genus with no absolute associations with clinical symptomatology. Here we analyzed fecal samples from Argentinean patients (. n=. 270) belonging to symptomatic (urticaria and non-specific gastrointestinal symptoms, n=. 39) and asymptomatic control (. n=. 28). Those patients infected with Blastocystis (. n=. 67) were submitted for morphological analysis, DNA extraction, 18S PCR, sequencing and STs identification according to DNA barcoding. Blastocystis vacuolar forms were the predominant morphotype (75%), ameboid-like forms were evidenced in 1.5% of samples. Blastocystis ST3 was detected in 71.6% (. n=. 48), of which 71.4%, (. n=. 35) and 28.6% (. n=. 14) belonged to symptomatic and asymptomatic respectively. Other subtypes identified were ST1 (14.9%), ST6 (7.5%) and ST2 (5.9%). Blastocystis 18S barcoding evidenced in non-urticaria symptomatic patients and asymptomatic control group the presence of allele 134 (ST3) (. p less than . 0.0001), while allele 34 (ST3) was detected in 85.7% (18/21) of symptomatic uricaria as compared with control group (1/21) (. p less than . 0.0001). The presence of a particular allele (. a34) significantly associated with urticaria patients was detected and the clinical implications of these findings are herein discussed. © 2015.